Initiating School Improvement: An Analysis of Improvement Priorities Issued by the Kentucky Department of Education - Courtney, Matthew (Journal of Interdisciplinary Studies in Education, 2022)
In the United States, state education agencies (SEAs) are required to regularly identify low performing schools. Initiating the school improvement process is one of the most important, yet most challenging steps. The Kentucky Department of Education (KDE) has been nationally recognized the way it initiates the school improvement process.  This study seeks to distill findings from 476 suggested first steps issued by the KDE to create action statements that a school leader could use when initiating school improvement on their own.School improvement audit reports were accessed from the KDE. Four hundred seventy six school improvement priorities (IPs) were coded using a two-tier conceptual coding protocol to distil IPs into essential improvement priorities (EIPs) that reflect the steps required to initiate school improvement.The coding protocol yielded 38 EIPs divided among eight themes. The most frequently assigned EIP relates the deployment of a consistent improvement process with the second most frequently assigned EIP being related to the establishment of a school-wide instructional process.Leaders of school with declining performance may use the EIPs identified by this study to inform their improvement efforts as they seek to enhance teaching and learning conditions in their school.